Enantiodivergent Deprotonation/Acylation of α‐Amino Nitriles1. Issue 49 (9th October 2013) - Sasaki, Michiko; Takegawa, Tomo; Sakamoto, Kunihiro; Kotomori, Yuri; Otani, Yuko; Ohwada, Tomohiko; Kawahata, Masatoshi; Yamaguchi, Kentaro; Takeda, Kei
<x xml:space="preserve">Abstract</x> Back to 'base'ics: The title reaction of enantioenriched α‐ureidonitriles was found to proceed in a highly enantiodivergent manner despite the intermediacy of stereolabile α‐nitrile metallocarbanions. Enantiodivergence is dependent upon the base used. For the less basic hexamethyldisilazides (HMDS), deprotonation in which a metal (M) cation is precomplexed with an electrophile is proposed. LDA=lithium diisopropylamide.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>